PENGARUH DISIPLIN KERJA, BEBAN KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI KELURAHAN DI KECAMATAN BANJARSARI KOTA SURAKARTA - Deni Eka Nurhidayatulloh; Abu Bakar Akbar (STKIP Subang, 2026)
The State Civil Apparatus (ASN) has a strategic role as the main executor in the delivery of public services; therefore, the performance produced is required to be effective, efficient, and of high quality. This study aims to analyze the influence of work discipline, workload, and organizational culture on the performance of urban village employees in Banjarsari District, Surakarta. This study employed a survey method involving urban village employees in Banjarsari District, Surakarta. The research population consisted of 147 employees, while the sample comprised 62 employees selected using a cluster sampling technique. Data were collected through questionnaires. The data analysis techniques included multiple linear regression analysis, t-test, F-test, and coefficient of determination test. Based on the research results, the validity and reliability tests indicated that all instruments were valid and reliable. The classical assumption tests showed that all variables met the required assumptions. The results of multiple linear regression analysis revealed that work discipline had a positive effect, workload had a positive effect, and organizational culture had a positive effect on performance, with the regression equation Y = 1.560 + 0.093X1 + 0.296X2 + 0.380X3 + e. The hypothesis testing results indicated that work discipline did not have a significant effect on employee performance, while workload and. organizational culture had significant effects on employee performance. The F-test results showed that the regression model used in this study was appropriate. The coefficient of determination test indicated that the independent variables explained 72.3% of the variation in the dependent variable, while the remaining 27.7% was influenced by other variables outside the model.